Stress-Strain-Temperature Behaviour of Deposited Cemented Slurry - Ting`, Wee Kiet (Universiti Malaysia Sarawak (UNIMAS), 2019)
In mine backfill design, the estimation of stress generation from the backfilling material is crucial to ensure the stablity of the underground structure and safety for the underground workers. Under elevation of temperature which may be caused by geothermal gradient and exothermic reaction of cement hydration, cemented paste backfill (CPB) was speculated to generate additional stress towards the confined surrounding. This thesis presents a series of experimental work to explain the mechanism of deposition within narrow wall in terms of stress-strain behaviour under thermal alteration. The physical and mechanical properties of the proposed material is studied. A model was designed and developed to investigate the stress-strain-temperature behaviour of CPB that fulfilled the necessary boundary condition to replicate a mining stope. Preliminary tests were conducted on the model to ensure its accuracy. CPB as the primary sample and uncemented paste backfill (UCPB) as control sample were studied regarding their stress-strain behaviour by applying different heating pattern during and after deposition. Both materials experienced thermal expansion when there is gain in temperature. Under semi-confined condition, the material will exert thermal stress onto the adjacent wall. The final stress can be up to 50% greater than the peak stress estimated by conventional theorem upon elevation of temperature by 30 ℃. UCPB and CPB experience different mechanism when there is a change in temperature but generally reflects the behaviour obtained from the full-scale monitoring. The test showed a good correlation with the anomaly observed within full-scale monitoring. Based on the finding, an empirical formulation is established to explain and predict the stress behaviour throughout the slurry-paste deposition.